1999
DOI: 10.1038/sj.bjp.0702585
|View full text |Cite
|
Sign up to set email alerts
|

Augmented acetylcholine‐induced, Rho‐mediated Ca2+ sensitization of bronchial smooth muscle contraction in antigen‐induced airway hyperresponsive rats

Abstract: Treatment with acetylcholine (ACh) of a b-escin-permeabilized intrapulmonary bronchial smooth muscle of the rat induced force when the Ca 2+ concentration was clamped at 1 mM. The AChinduced Ca 2+ sensitization of myo®laments was signi®cantly greater in antigen-induced airway hyperresponsive rats than in control rats. The ACh-induced Ca 2+ sensitization was completely blocked by treatment with Clostridium botulinum C3 exoenzyme, an inactivator of Rho family of proteins. Moreover, the protein level of RhoA in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
213
1
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(233 citation statements)
references
References 15 publications
(30 reference statements)
14
213
1
5
Order By: Relevance
“…Similarly, an increased responsiveness of bronchial smooth muscle has been demonstrated in a rat model of AHR induced by repeated antigen inhalation (Chiba and Misawa, 1995a, b). In AHR rats, it has also been demonstrated that acetylcholine-induced RhoA-mediated Ca 2+ sensitization is markedly augmented concomitantly with an increased expression of RhoA protein in the bronchial smooth muscle (Chiba et al, 1999b). It is thus possible that the upregulation of RhoA protein in airway smooth muscle might be an essential event in the pathogenesis of AHR.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, an increased responsiveness of bronchial smooth muscle has been demonstrated in a rat model of AHR induced by repeated antigen inhalation (Chiba and Misawa, 1995a, b). In AHR rats, it has also been demonstrated that acetylcholine-induced RhoA-mediated Ca 2+ sensitization is markedly augmented concomitantly with an increased expression of RhoA protein in the bronchial smooth muscle (Chiba et al, 1999b). It is thus possible that the upregulation of RhoA protein in airway smooth muscle might be an essential event in the pathogenesis of AHR.…”
Section: Introductionmentioning
confidence: 92%
“…Male Wistar rats (6 weeks of age, specific pathogen-free, 170-190 g, Charles River Japan, Inc.) were sensitized and repeatedly challenged with 2,4-dinitrophenylated Ascaris suum antigen (DNP-Asc) by the method described in our previous papers (Chiba & Misawa, 1995a,b;Chiba et al, 1999b). Age-matched non-sensitized normal animals were used as controls (Chiba and Misawa, 1995a,b;Chiba et al, 1999b).…”
Section: Sensitization and Antigenic Challengementioning
confidence: 99%
See 2 more Smart Citations
“…Cytokines enhance ASM calcium sensitivity and contraction through a signaling pathway involving NF-κB, ras homolog gene family, member A (RhoA), and ROCK2 (2)(3)(4). Activation of this pathway leads to phosphorylation and inactivation of MLC phosphatase (MLCP) by ROCK2 (4,7,8).…”
mentioning
confidence: 99%